Smart cities and circular economy : the future of sustainable urban development - Kandpal, Vinay; Santibanez-Gonzalez, Ernesto Dr; Chatterjee, Prasenjit; Nallpaneni, Manoj Kumar (Emmerald Publishing Limited, 2024)
Addressing resource depletion and environmental concerns for sustainable urban living, Smart Cities and Circular Economy unveils the transformative potential and challenges of integrating these ideas while emphasizing environmental, social, and economic benefits